2022
DOI: 10.1111/jam.15488
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional diversity of Dendrobium officinale microbiome in Danxia habitat

Abstract: Aims Microbial communities that inhabit plants are crucial for plant survival and well‐being including growth in stressful environments. The medicinal plant, Dendrobium officinale grows in the barren soils of the Danxia Habitat. However, the microbiome composition and functional potential for growth of this plant in this environment are still unexplored. Methods and Results In this study, we analysed the taxonomic and functional diversity of the D. officinale Microbiome by metagenomic sequencing of both rhizos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In addition, phenolic acids and their derivatives including syringic acid, dihydro ferulic acid tyramine, p-hydroxybenzoic acid, ellagic acid, and gallotannins were also discovered in DO. These PPs were shown to have various biological activities, such as antioxidant, hypoglycemic, anticancer, antimicrobial, and immunomodulatory activities ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phenolic acids and their derivatives including syringic acid, dihydro ferulic acid tyramine, p-hydroxybenzoic acid, ellagic acid, and gallotannins were also discovered in DO. These PPs were shown to have various biological activities, such as antioxidant, hypoglycemic, anticancer, antimicrobial, and immunomodulatory activities ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that endophytic fungi of D. officinale mainly include 57 genera of Basidiomycota, Ascomycota and Deuteromycotina, and endophytic bacteria mainly include 50 genera of Firmicutes, Proteobacteria, Actinobacteria, Bacteroidetes and Fusobacteria ( Santoyo et al 2016 ; Sarsaiya et al 2020 ; Wang et al 2022 ; Zhang et al 2019 ). In this study, the endophytic fungi in the roots of D. officinale were mainly Basidiomycota and Ascomycota, and the endophytic bacteria were mainly Proteobacteria, Actinomycetes, Firmicutes, Bacteroides, Acidobacteria, etc.…”
Section: Discussionmentioning
confidence: 99%